Hyperammonemic Encephalopathy and Thyroid Storm Leading to Coma: A Case Report - Tung Phi Nguyen; Thang Trong Khong; Tuan Duc Tran (Case Reports in Critical Care)
Hyperammonemic encephalopathy is a rare but serious condition often linked to hepatic dysfunction or metabolic disorders. Thyroid storm is an endocrine emergency that can cause profound metabolic disturbances, though its relationship with hyperammonemia remains unclear. We report a unique case of a 33-year-old previously healthy male who developed progressive fatigue, nausea, and vomiting, followed by acute neurological deterioration. Initial evaluation revealed hyperammonemia (284 μmol/L) and thyrotoxicosis (fT4: 27 pmol/L and TSH: 0.007 μIU/mL), with no hepatic dysfunction. His neurological status declined from GCS 12 to GCS 7 within hours. Brain MRI and cerebrospinal fluid analysis were unremarkable. The patient was diagnosed with coma in the setting of hyperammonemic encephalopathy and thyroid storm. Management included propylthiouracil, Lugol’s iodine, propranolol, hydrocortisone, and continuous renal replacement therapy (CRRT). His ammonia levels significantly improved within 48 h, leading to rapid clinical improvement and extubation. This case highlights the importance of recognizing hyperammonemia as a potential cause of altered mental status, even in the absence of hepatic dysfunction, and raises questions about potential but unestablished links between thyroid dysfunction and ammonia metabolism.